Community engagement with genetics: public perceptions and expectations about genetics research. (23rd August 2013) - Etchegary, Holly; Green, Jane; Parfrey, Patrick; Street, Catherine; Pullman, Daryl
Abstract: Background: Knowledge of molecular biology and genomics continues to expand rapidly, promising numerous opportunities for improving health. However, a key aspect of the success of genomic medicine is related to public understanding and acceptance. Design: Using community consultations and an online survey, we explored public attitudes and expectations about genomics research. Results: Thirty‐three members of the general public in Newfoundland, Canada, took part in the community sessions, while 1024 Atlantic Canadians completed the online survey. Overall, many participants noted they lacked knowledge about genetics and associated research and took the opportunity to ask numerous questions throughout sessions. Participants were largely hopeful about genomics research in its capacity to improve health, not only for current residents, but also for future generations. However, they did not accept such research uncritically, and a variety of complex issues and questions arose during the community consultations and were reflected in survey responses. Discussion: With the proliferation of biobanks and the rapid pace of discoveries in genomics research, public support will be crucial to realize health improvements. If researchers can engage the public in regular, transparent dialogue, this two‐way communication could allow greater understanding of the research process and the design of efficient and effective genetic health services, informed by the public that will use them.